SMALL FARM RESERVOIR AS A SUPPLEMENTAL IRRIGATION SOURCE FOR CROPS PLANTED ON MARGINAL LAND - Hafif, Bariot; Murni, Andarias Makka (AGRIVITA, Journal of Agricultural Science, 2012)
Rainwater harvesting is a water conservation measures. Water is harvested in addition to reducing runoff, and erosion control can be used as a supplemental source of irrigation for crops on marginal land. A study was conducted to test the effectiveness of a small pool of rainwater harvesting usually termed as a small farm reservoir (SFRs) as a complementary source of irrigation water in improving the productivity of farming on marginal land. The experiment was conducted from December 2005 to August 2007 in Buanasakti, East Lampung, Indonesia. Three SFRs with a volume of 7 x 3 x 2.5 m (50 m3 were made ââon upland at sloping area (8-15%) of ââ1.5 ha. Further rain was deposited to be used by farmers for crop watering, especially in the early dry season. Extensive planting of crops that can be irrigated with SFRs, based on consideration of the farmers themselves. Observation result indicated that the SFRs were used by the farmers to water the vegetables and tobacco plants with different extents. However, on average, the presence of SFRs increased the planting area of vegetables such as beans and cucumbers in the dry season to 650%. Increased intensity of cultivation of vegetables and tobacco cultivation also increase farmers income of 1.5 ha of marginal land as much as 37.49%.   Keywords: small farm reservoir, supplemental irrigation, vegetables, marginal land